2004
DOI: 10.1177/1049732303259803
|View full text |Cite
|
Sign up to set email alerts
|

“Here’s What I’d Do …”: Condom Promotion Strategies Proposed by High-Risk Women in Anchorage, Alaska

Abstract: Women drug users are at significant risk of sexually transmitted HIV; however, interventions aimed at increasing condom use by this population have been relatively ineffective. The authors conducted a series of focus groups with 17 current and former drug-using women to identify (a) reasons for using versus not using condoms, (b) intervention strategies they believed would be most effective at increasing condom use, and (c) previous ineffective intervention strategies. Risk of HIV, sexually transmitted disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For instance, Kalichman, Williams, and Nachimson (1999; see also Kalichman, Kelly, Hunter, Murphy, & Tyler, 1993) reported positive results from a brief behavioral-skills-building intervention in which African American females with expertise in public health education and prevention of STIs (Sexually Transmitted Infections) were selected to reach other African American females (see also Bichsel, 1998; Dalton, 2001; Dyche & Zayas, 1995; Frost-Pineda, Van Susteren, & Gold, 2004; Nikelly, 1997). However, in the opinion of a sample of Alaskan women at risk for HIV infection, to be effective, outreach workers need not be similar to targets with respect to race, gender, or age, but do need to be pleasant and have similar life experiences to the targets (Fenaughty & Namyniuk, 2004). In addition, in a study with teens by Jemmott et al (1998), matching the ethnicity of leaders and the target youth was unrelated to the effectiveness of interventions for African American youth, even though matching age is reportedly important for teen audiences (Kalafat & Elias, 1994; Milburn, 1995; Myrick & Folk, 1991; Myrick, 1996; Ozer, Weinstein, Maslack, & Siegel, 1997; Philliber, 1999; Reeder, Pryor, & Harsh, 1997; Stuart, Waalen, & Haelstromm, 2003; Tindal & Salmon-White, 1990; Wolf, Bond, & Tawfik, 2000; but see Department for Education and Skills, U.K., 2000).…”
Section: Hypotheses About Differential Effectiveness Of the Intervent...mentioning
confidence: 99%
“…For instance, Kalichman, Williams, and Nachimson (1999; see also Kalichman, Kelly, Hunter, Murphy, & Tyler, 1993) reported positive results from a brief behavioral-skills-building intervention in which African American females with expertise in public health education and prevention of STIs (Sexually Transmitted Infections) were selected to reach other African American females (see also Bichsel, 1998; Dalton, 2001; Dyche & Zayas, 1995; Frost-Pineda, Van Susteren, & Gold, 2004; Nikelly, 1997). However, in the opinion of a sample of Alaskan women at risk for HIV infection, to be effective, outreach workers need not be similar to targets with respect to race, gender, or age, but do need to be pleasant and have similar life experiences to the targets (Fenaughty & Namyniuk, 2004). In addition, in a study with teens by Jemmott et al (1998), matching the ethnicity of leaders and the target youth was unrelated to the effectiveness of interventions for African American youth, even though matching age is reportedly important for teen audiences (Kalafat & Elias, 1994; Milburn, 1995; Myrick & Folk, 1991; Myrick, 1996; Ozer, Weinstein, Maslack, & Siegel, 1997; Philliber, 1999; Reeder, Pryor, & Harsh, 1997; Stuart, Waalen, & Haelstromm, 2003; Tindal & Salmon-White, 1990; Wolf, Bond, & Tawfik, 2000; but see Department for Education and Skills, U.K., 2000).…”
Section: Hypotheses About Differential Effectiveness Of the Intervent...mentioning
confidence: 99%
“…These factors are categorized across many dimensions, including drug and alcohol use (Poulin & Graham, 2001; Roberts & Kennedy, 2006), relationship/intimacy factors (Aalsma, Fortenberry, Sayegh, & Orr, 2006; Civic, 1999; Prince & Bernard, 1998), pleasure and performance issues (Crosby, Graham, Yarber, & Sanders, 2004), cultural beliefs about condom use and transmission of infection (Braithwaite & Thomas, 2001; Duncan, Harrison, Toldson, Malaka, & Sithole, 2005), low perceived susceptibility (Civic, 2000; Opt & Loffredo, 2004), lack of preparation (van Empelen & Kok, 2008) and poor access or lack of availability (Fenaughty & Namyniuk, 2004; Sneed et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…We were somewhat surprised to discover that almost all of the substance userelated measures we examined were unrelated to condom use self-efficacy, especially since so many previous studies have shown a link between drug use and condom use, attitudes toward condom use, and condom use self-efficacy (see, for example, Elwood & Vega, 2005;Fenaughty & Namyniuk, 2004;Tucker, Wenzel, Elliott, Marshall, & Williamson, 2004). Nevertheless, one such measure-previously having been in a drug treatment program-was found to be a significant predictor of condom use self-efficacy in this population of young adult users of ecstasy.…”
Section: Discussionmentioning
confidence: 95%